Hemolytic uremic syndrome in the setting of COVID-19 successfully treated with complement inhibition therapy: An instructive case report of a previously healthy toddler and review of literature - Matošević, Matija; Kos, Ivanka; Davidović, Maša; Ban, Maja; Matković, Hana; Jakopčić, Ivan; Vuković Brinar, Ivana; Szilágyi, Ágnes; Csuka, Dorottya; Sinkovits, György; Prohászka, Zoltán; Vrljičak, Kristina; et al. (Frontiers in Pediatrics, 2023)
Introduction: As the global pandemic continues, new complications of COVID-19 in pediatric population have turned up, one of them being hemolytic uremic syndrome (HUS), a complement-mediated thrombotic microangiopathy (CM-TMA) characterized by triad of thrombocytopenia, microangiopathic hemolytic anemia and acute kidney injury (AKI). With both multisystem inflammatory syndrome in children (MIS-C) and HUS sharing complement dysregulation as one of the key factors, the aim of this case report is to highlight differences between these two conditions and also emphasize the importance of complement blockade as a treatment modality. Case report: We describe a 21-month-old toddler who initially presented with fever and confirmed COVID-19. His condition quickly deteriorated and he developed oliguria, accompanied with diarrhea, vomiting and oral intake intolerance. HUS was suspected, supported with compelling laboratory findings, including decreased platelets count and C3 levels, elevated LDH, urea, serum creatinine and sC5b-9 and presence of schistocytes in peripheral blood, negative fecal Shiga toxin and normal ADAMTS13 metalloprotease activity. The patient was given C5 complement blocker Ravulizumab and started to display rapid improvement. Conclusion: Although reports of HUS in the setting of COVID-19 continue to pour in, the questions of exact mechanism and similarities to MIS-C remain. Our case for the first time accentuates the use of complement blockade as a valuable treatment option in this scenario. We sincerely believe that reporting on HUS as a complication of COVID-19 in children will give rise to improved diagnosis and treatment, as well as better understanding of both of these intricating diseases.